Define a function. What do you mean by the domain and range of a function? Give examples.
Definition:A relation R from a set A to a set B is called a function if each element of A has a unique image in B.
It is denoted by the symbol f:A→B which reads ‘f’ is a function from A to B ‘f’ maps A to B.
Let f:A→B,then the set A is known as the domain of f & the set B is known as co - domain of f .The set of images of all the elements of A is known as the range of f.
Thus, Domain of f = {a|a ∈ A,(a,f(a)) ∈ f )
Range of f = {f(a) | a∈ A ,f(a) ∈ B }
Example: The domain of y = sin x is all values of x i.e. R , since there are no restrictions on the values for x. The range of y is betweeen −1 and 1. We could write this as −1 ≤ y ≤ 1.
Define each of the following:
(i) injective function
(ii) surjective function
(iii) bijective function
(iv) many - one function
(v) into function
Give an example of each type of functions.
1)injective function
Definition: A function f: A → B is said to be a one - one function or injective mapping if different elements of A have different f images in B.
A function f is injective if and only if whenever f(x) = f(y), x = y.
Example: f(x) = x + 9 from the set of real number R to R is an injective function. When x = 3,then :f(x) = 12,when f(y) = 8,the value of y can only be 3,so x = y.
(ii) surjective function
Definition: If the function f:A→B is such that each element in B (co - domain) is the ‘f’ image of atleast one element in A , then we say that f is a function of A ‘onto’ B .Thus f: A→B is surjective if, for all b∈B, there are some a∈A such that f(a) = b.
Example: The function f(x) = 2x from the set of natural numbers N to the set of non negative even numbers is a surjective function.
(iii) bijective function
Definition: A function f (from set A to B) is bijective if, for every y in B, there is exactly one x in A such that f(x) = y.Alternatively, f is bijective if it is a one - to - one correspondence between those sets, in other words, both injective and surjective.
Example: If f(x) = x2,from the set of positive real numbers to positive real numbers is both injective and surjective.Thus it is a bijective function.
(iv)many - one function
Defintion : A function f: A→B is said to be a many one functions if two or more elements of A have the same f image in B.
trigonometric functions such as sinx are many - to - one since sinx = sin(2 + x) = sin(4 + x) and so one…
(v) into function
Definition: If f:A→B is such that there exists atleast one element in co - domain , which is not the image of any element in the domain , then f(x) is into.
Let f(x) = y = x – 1000
⇒ x = y + 1000 = g(y) (say)
Here g(y) is defined for each y∈ I , but g(y) ∉ N for y ≤ − 1000. Hence,f is into.
Give an example of a function which is
(i) one - one but not onto
(ii) one - one and onto
(iii) neither one - one nor onto
(iv) onto but not one - one.
(i) one - one but not onto
f(x) = 6x
For One - One
f(x1) = 6x1
f(x2) = 6x2
put f(x1) = f(x2) we get
6x1 = 6x2
Hence, if f(x1) = f(x2) , x1 = x2
Function f is one - one
For Onto
f(x) = 6x
let f(x) = y ,such that y∈N
6x = y
⇒
If y = 1
x =
which is not possible as x∈N
Hence, f is not onto.
(ii) one - one and onto
f(x) = x5
⇒y = x5
Since the lines do not cut the curve in 2 equal valued points of y, therefore, the function f(x) is one - one.
The range of f(x) = ( - ∞,∞) = R(Codomain)
∴f(x) is onto
∴f(x) is one - one and onto.
(iii) neither one - one nor onto
f(x) = x2
for one one:
f(x1) = (x1)2
f(x2) = (x2)2
f(x1) = f(x2)
⇒(x1)2 = (x2)2
⇒x1 = x2 or x1 = - x2
Since x1 does not have a unique image it is not one - one
For onto
f(x) = y
such that y∈R
x2 = y
⇒x =
If y is negative under root of a negative number is not real
Hence,f(x) is not onto.
∴f(x) is neither onto nor one - one
(iv) onto but not one - one.
Consider a function f:Z→N such that f(x) = |x|.
Since the Z maps to every single element in N twice, this function is onto but not one - one.
Z - integers
N - natural numbers.
Let f : R → R be defined by
Find (i) f(2) (ii) f(4) (iii) f( - 1) (iv) f( - 3).
i)f(2)
Since f(x) = x2 - 2 , when x = 2
∴ f(2) = (2)2 - 2 = 4 - 2 = 2
∴f(2) = 2
ii)f(4)
Since f(x) = 3x - 1 , when x = 4
∴f(4) = (3×4) - 1 = 12 - 1 = 11
∴f(4) = 11
iii)f( - 1)
Since f(x) = x2 - 2 , when x = - 1
∴ f( - 1) = ( - 1)2 - 2 = 1 - 2 = - 1
∴f( - 1) = - 1
iv)f( - 3)
Since f(x) = 2x + 3 , when x = - 3
∴f( - 3) = 2×( - 3) + 3 = - 6 + 3 = - 3
∴f( - 3) = - 3
Show that the function f: R → R : f(x) = 1 + x2 is many - one into.
To show: f: R → R : f(x) = 1 + x2 is many - one into.
Proof:
f(x) = 1 + x2
⇒y = 1 + x2
Since the lines cut the curve in 2 equal valued points of y therefore the function f(x) is many one.
The range of f(x) = [1,∞)≠R(Codomain)
∴f(x) is not onto
⇒f(x) is into
Hence, showed that f: R → R : f(x) = 1 + x2 is many - one into.
Show that the function f : R → R : f(x) = x4 is many - one and into.
To show: f: R → R : f(x) = x4 is many - one into.
Proof:
f(x) = x4
⇒y = x4
Since the lines cut the curve in 2 equal valued points of y, therefore, the function f(x) is many ones.
The range of f(x) = [0,∞)≠R(Codomain)
∴f(x) is not onto
⇒f(x) is into
Hence, showed that f: R → R : f(x) = x4 is many - one into.
Show that the function f: R → R : f(x) = x5 is one - one and onto.
To show: f: R → R : : f(x) = x5 is one - one and onto.
Proof:
f(x) = x5
⇒y = x5
Since the lines do not cut the curve in 2 equal valued points of y, therefore, the function f(x) is one - one.
The range of f(x) = ( - ∞,∞) = R(Codomain)
∴f(x) is onto
Hence, showed f: R → R : f(x) = x5 is one - one and onto.
Let and Show that each one of f and g is one - one but (f + g) is not one - one.
Here in this range, the lines do not cut the curve in 2 equal valued points of y, therefore, the function f(x) = sinx is one - one.
in this range, the lines do not cut the curve in 2 equal valued points of y, therefore, the function f(x) = cosx is also one - one.
(f + g):[0,] →R = sinx + cosx
in this range the lines cut the curve in 2 equal valued points of y, therefore, the function f(x) = cosx + sinx is not one - one.
Hence,showed that each one of f and g is one - one but (f + g) is not one - one.
Show that the function
(i) f : N → N : f(x) = x2 is one - one into.
(ii) f : Z → Z : f(x) = x2 is many - one into
(i) f : N → N : f(x) = x2 is one - one into.
f(x) = x2
⇒y = x2
Since the function f(x) is monotonically increasing from the domain N → N
∴f(x) is one –one
Range of f(x) = (0,∞)≠N(codomain)
∴f(x) is into
∴f : N → N : f(x) = x2 is one - one into.
(ii) f : Z → Z : f(x) = x2 is many - one into
f(x) = x2
⇒y = x2
in this range the lines cut the curve in 2 equal valued points of y, therefore, the function f(x) = x2 is many - one .
Range of f(x) = (0,∞)≠Z(codomain)
∴f(x) is into
∴ f : Z → Z : f(x) = x2 is many - one into
Show that the function
(i) f : N → N : f(x) = x3 is one - one into
(ii) f : Z → Z : f(x) = x3 is one - one into
(i) f : N → N : f(x) = x3 is one - one into.
f(x) = x3
Since the function f(x) is monotonically increasing from the domain N → N
∴f(x) is one –one
Range of f(x) = ( - ∞,∞)≠N(codomain)
∴f(x) is into
∴f : N → N : f(x) = x2 is one - one into.
(ii) f : Z → Z : f(x) = x3 is one - one into
f(x) = x3
Since the function f(x) is monotonically increasing from the domain Z → Z
∴f(x) is one –one
Range of f(x) = ( - ∞,∞)≠Z(codomain)
∴f(x) is into
∴ f : Z → Z : f(x) = x3 is one - one into.
Show that the function f : R → R : f(x) = sin x is neither one - one nor onto.
f(x) = sinx
y = sinx
Here in this range, the lines cut the curve in 2 equal valued points of y, therefore, the function f(x) = sinx is not one - one.
Range of f(x) = [ - 1,1]≠R(codomain)
∴f(x) is not onto.
Hence, showed that the function f : R → R : f(x) = sin x is neither one - one nor onto.
Prove that the function f : N → N : f(n) = (n2 + n + 1) is one - one but not onto.
In the given range of N f(x) is monotonically increasing.
∴f(n) = n2 + n + 1 is one one.
But Range of f(n) = [0.75,∞)≠N(codomain)
Hence,f(n) is not onto.
Hence, proved that the function f : N → N : f(n) = (n2 + n + 1) is one - one but not onto.
Show that the function f: N → Z, defined by
is both one - one and onto.
f(1) = 0
f(2) = - 1
f(3) = 1
f(4) = - 2
f(5) = 2
f(6) = - 3
Since at no different values of x we get same value of y ∴f(n) is one –one
And range of f(n) = Z = Z(codomain)
∴ the function f: N → Z, defined by
is both one - one and onto.
Find the domain and range of the function
F : R → R : f(x) = x2 + 1.
Since the function f(x) can accept any values as per the given domain R, therefore, the domain of the function f(x) = x2 + 1 is R.
The minimum value of f(x) = 1
⇒Range of f(x) = [ - 1,∞]
i.e range (f) = {y ∈ R : y ≥ 1}
Ans: dom (f) = R and range (f) = {y ∈ R : y ≥ 1}
Which of the following relations are functions? Give reasons. In case of a function, find its domain and range.
(i) f = {( - 1, 2), (1, 8), (2, 11), (3, 14)}
(ii) g = {(1, 1), (1, - 1), (4, 2), (9, 3),
(16, 4)}
(iii) h = {(a, b), (b, c), (c, b), (d, c)}
For a relation to be a function each element of 1st set should have different image in the second set(Range)
i) (i) f = {( - 1, 2), (1, 8), (2, 11), (3, 14)}
Here, each of the first set element has different image in second set.
∴f is a function whose domain = { - 1, 1, 2, 3} and range (f) = {2, 8, 11, 14}
(ii) g = {(1, 1), (1, - 1), (4, 2), (9, 3),
(16, 4)}
Here, some of the first set element has same image in second set.
∴ g is not a function.
(iii) h = {(a, b), (b, c), (c, b), (d, c)}
Here, each of the first set element has different image in second set.
∴h is a function whose domain = {a, b, c, d} and range (h) = {b, c}
(range is the intersection set of the elements of the second set elements.)
Find the domain and range of the real function, defined by Show that f is many - one.
For domain (1 + x2)≠0
⇒x2≠ - 1
⇒dom(f) = R
For the range of x:
⇒
ymin = 0 (when x = 0)
ymax = 1 (when x = ∞)
∴range of f(x) = [0,1)
For many one the lines cut the curve in 2 equal valued points of y therefore the function f(x) is many - one.
Ans:
dom(f) = R
range(f) = [0,1)
function f(x) is many - one.
Show that the function
is many - one into.
Find (i) (ii) (iii)
(iv)
(i)
Here, x = 1/2,which is rational
∴f(1/2) = 1
(ii)
Here, x = √2,which is irrational
∴f(√2) = - 1
(iii)
Here, x = ∏, which is irrational
= - 1
(iv)
Here,x = 2 +√3, which is irrational
∴f(2 +√3) = - 1
Ans. (i) 1 (ii) - 1 (iii) - 1 (iv) - 1
Let A = {1, 2, 3, 4}. Let f : A → A and g : A → A,
defined by f = {(1, 4), (2, 1), (3,3),(4, 2)} and g = {(1, 3), (2, 1), (3, 2), (4, 4)}.
Find (i) g of (ii) f o g (iii) f o f.
(i) g o f
To find: g o f
Formula used: g o f = g(f(x))
Given: f = {(1, 4), (2, 1), (3, 3), (4, 2)} and g = {(1, 3), (2, 1),
(3, 2), (4, 4)}
Solution: We have,
gof(1) = g(f(1)) = g(4) = 4
gof(2) = g(f(2)) = g(1) = 3
gof(3) = g(f(3)) = g(3) = 2
gof(4) = g(f(4)) = g(2) = 1
Ans) g o f = {(1, 4), (2, 3), (3, 2), (4, 1)}
(ii) f o g
To find: f o g
Formula used: f o g = f(g(x))
Given: f = {(1, 4), (2, 1), (3, 3), (4, 2)} and g = {(1, 3), (2, 1),
(3, 2), (4, 4)}
Solution: We have,
fog(1) = f(g(1)) = f(3) = 3
fog(2) = f(g(2)) = f(1) = 4
fog(3) = f(g(3)) = f(2) = 1
fog(4) = f(g(4)) = f(4) = 2
Ans) f o g = {(1, 3), (2, 4), (3, 1), (4, 2)}
(iii) f o f
To find: f o f
Formula used: f o f = f(f(x))
Given: f = {(1, 4), (2, 1), (3, 3), (4, 2)}
Solution: We have,
fof(1) = f(f(1)) = f(4) = 2
fof(2) = f(f(2)) = f(1) = 4
fof(3) = f(f(3)) = f(3) = 3
fof(4) = f(f(4)) = f(2) = 1
Ans) f o f = {(1, 2), (2, 4), (3, 3), (4, 1)}
Let f : {3, 9, 12} → {1, 3, 4} and g : {1, 3, 4, 5} → {3, 9} be
defined as f = {(3, 1), (9, 3), (12, 4)} and
g = {(1, 3), (3, 3), (4, 9), (5, 9)}.
Find (i) (g o f) (ii) (f o g).
(i) g o f
To find: g o f
Formula used: g o f = g(f(x))
Given: f = {(3, 1), (9, 3), (12, 4)} and g = {(1, 3), (3, 3),(4, 9), (5, 9)}
Solution: We have,
gof(3) = g(f(3)) = g(1) = 3
gof(9) = g(f(9)) = g(3) = 3
gof(12) = g(f(12)) = g(4) = 9
Ans) g o f = {(3, 3), (9, 3), (12, 9)}
(ii) f o g
To find: f o g
Formula used: f o g = f(g(x))
Given: f = {(3, 1), (9, 3), (12, 4)} and g = {(1, 3), (3, 3),(4, 9), (5, 9)}
Solution: We have,
fog(1) = f(g(1)) = f(3) = 1
fog(3) = f(g(3)) = f(3) = 1
fog(4) = f(g(4)) = f(9) = 3
fog(5) = f(g(5)) = f(9) = 3
Ans) f o g = {(1, 1), (3, 1), (4, 3), (5, 3)}
Let f : R → R : f(x) = x2 and g : R → R : g(x) = (x + 1).
Show that (g o f) ≠ (f o g).
To prove: (g o f) ≠ (f o g)
Formula used: (i) g o f = g(f(x))
(ii) f o g = f(g(x))
Given: (i) f : R → R : f(x) = x2
(ii) g : R → R : g(x) = (x + 1)
Proof: We have,
g o f = g(f(x)) = g(x2) = ( x2 + 1 )
f o g = f(g(x)) = g(x+1) = [ (x+1)2 + 1 ] = x2 + 2x + 2
From the above two equation we can say that (g o f) ≠ (f o g)
Hence Proved
Let f : R → R : f(x) = (2x + 1) and g : R → R : g(x) = (x2 - 2).
Write down the formulae for
(i) (g o f) (ii) (f o g)
(iii) (f o f) (iv) (g o g)
(i) g o f
To find: g o f
Formula used: g o f = g(f(x))
Given: (i) f : R → R : f(x) = (2x + 1)
(ii) g : R → R : g(x) = (x2 - 2)
Solution: We have,
g o f = g(f(x)) = g(2x + 1) = [ (2x + 1)2 – 2 ]
⇒ 4x2 + 4x + 1 – 2
⇒ 4x2 + 4x – 1
Ans). g o f (x) = 4x2 + 4x – 1
(ii) f o g
To find: f o g
Formula used: f o g = f(g(x))
Given: (i) f : R → R : f(x) = (2x + 1)
(ii) g : R → R : g(x) = (x2 - 2)
Solution: We have,
f o g = f(g(x)) = f(x2 - 2) = [ 2(x2 - 2) + 1 ]
⇒ 2x2 - 4 + 1
⇒ 2x2 – 3
Ans). f o g (x) = 2x2 – 3
(iii) f o f
To find: f o f
Formula used: f o f = f(f(x))
Given: (i) f : R → R : f(x) = (2x + 1)
Solution: We have,
f o f = f(f(x)) = f(2x + 1) = [ 2(2x + 1) + 1 ]
⇒ 4x + 2 + 1
⇒ 4x + 3
Ans). f o f (x) = 4x+ 3
(iv) g o g
To find: g o g
Formula used: g o g = g(g(x))
Given: (i) g : R → R : g(x) = (x2 - 2)
Solution: We have,
g o g = g(g(x)) = g(x2 - 2) = [ (x2 - 2)2 – 2]
⇒ x4 -4x2 + 4 - 2
⇒ x4 -4x2 + 2
Ans). g o g (x) = x4 -4x2 + 2
Let f : R → R : f(x) = (x2 + 3x + 1) and g: R → R : g(x) = (2x - 3). Write down the formulae for
(i) g o f
(ii) f o g
(iii) g o g
(i) g o f
To find: g o f
Formula used: g o f = g(f(x))
Given: (i) f : R → R : f(x) = (x2 + 3x + 1)
(ii) g: R → R : g(x) = (2x - 3)
Solution: We have,
g o f = g(f(x)) = g(x2 + 3x + 1) = [ 2(x2 + 3x + 1) – 3 ]
⇒ 2x2 + 6x + 2 – 3
⇒ 2x2 + 6x – 1
Ans). g o f (x) = 2x2 + 6x – 1
(ii) f o g
To find: f o g
Formula used: f o g = f(g(x))
Given: (i) f : R → R : f(x) = (x2 + 3x + 1)
(ii) g: R → R : g(x) = (2x - 3)
Solution: We have,
f o g = f(g(x)) = f(2x - 3) = [ (2x - 3)2 + 3(2x – 3) + 1 ]
⇒ 4x2 - 12x + 9 + 6x – 9 + 1
⇒ 4x2 - 6x + 1
Ans). f o g (x) = 4x2 - 6x + 1
(iii) g o g
To find: g o g
Formula used: g o g = g(g(x))
Given: (i) g: R → R : g(x) = (2x - 3)
Solution: We have,
g o g = g(g(x)) = g(2x - 3) = [ 2(2x – 3) - 3 ]
⇒ 4x – 6 - 3
⇒ 4x - 9
Ans). g o g (x) = 4x – 9
Let f : R → R : f(x) = |x|, prove that f o f = f.
To prove: f o f = f
Formula used: f o f = f(f(x))
Given: (i) f : R → R : f(x) = |x|
Solution: We have,
f o f = f(f(x)) = f(|x|) = = |x| = f(x)
Clearly f o f = f.
Hence Proved.
Let f : R → R : f(x) = x2, g : R → R : g(x) = tan x
and h : R → R : h(x) = log x.
Find a formula for h o (g o f).
Show that [h o (g o f)]
|
To find: formula for h o (g o f)
To prove:
Formula used: f o f = f(f(x))
Given: (i) f : R → R : f(x) = x2
(ii) g : R → R : g(x) = tan x
(iii) h : R → R : h(x) = log x
Solution: We have,
h o (g o f) = h o g(f(x)) = h o g(x2)
= h(g(x2)) = h (tan x2)
= log (tan x2)
h o (g o f) = log (tan x2)
For,
= 0
Hence Proved.
Let f : R → R : f(x) (2x - 3) and
Show that (f o g) = IR = (g o f).
To prove: (f o g) = IR = (g o f).
Formula used: (i) f o g = f(g(x))
(ii) g o f = g(f(x))
Given: (i) f : R → R : f(x) = (2x - 3)
(ii)
Solution: We have,
f o g = f(g(x))
= x + 3 – 3
= x
= IR
g o f = g(f(x))
=
= x
= IR
Clearly we can see that (f o g) = IR = (g o f) = x
Hence Proved.
Let f : Z → Z : f(x) = 2x. Find g : Z → Z : g o f = IZ.
To find: g : Z → Z : g o f = IZ
Formula used: (i) f o g = f(g(x))
(ii) g o f = g(f(x))
Given: (i) g : Z → Z : g o f = IZ
Solution: We have,
f(x) = 2x
Let f(x) = y
⇒ y = 2x
Where g: Z → Z
For g o f,
⇒ g(f(x))
⇒ g(2x)
⇒ x = IZ
Clearly we can see that (g o f) = x = IZ
Let f : N → N : f(x) = 2x, g : N → N : g(y) = 3y + 4 and h : N → N : h(z) = sin z. Show that h o (g o f ) = (h o g) o f.
To show: h o (g o f ) = (h o g) o f
Formula used: (i) f o g = f(g(x))
(ii) g o f = g(f(x))
Given: (i) f : N → N : f(x) = 2x
(ii) g : N → N : g(y) = 3y + 4
(iii) h : N → N : h(z) = sin z
Solution: We have,
LHS = h o (g o f )
⇒ h o (g(f(x))
⇒ h(g(2x))
⇒ h(3(2x) + 4)
⇒ h(6x +4)
⇒ sin(6x + 4)
RHS = (h o g) o f
⇒ (h(g(x))) o f
⇒ (h(3x + 4)) o f
⇒ sin(3x+4) o f
Now let sin(3x+4) be a function u
RHS = u o f
⇒ u(f(x))
⇒ u(2x)
⇒ sin(3(2x) + 4)
⇒ sin(6x + 4) = LHS
Hence Proved.
If f be a greatest integer function and g be an absolute value function, find the value of
Formula used: (i) f o g = f(g(x))
(ii) g o f = g(f(x))
Given: (i) f is a greatest integer function
(ii) g is an absolute value function
f(x) = [x] (greatest integer function)
g(x) = (absolute value function)
Substituting values from (i) and (ii)
⇒ [1.5] +
⇒ 1 + 1 = 2
Ans) 2
Let f : R → R : f(x) = x2 + 2 and find f o g and g o f and hence find (f o g) (2) and (g o f) (-3).
To find: f o g, g o f ,(f o g) (2) and (g o f) (-3)
Formula used: (i) f o g = f(g(x))
(ii) g o f = g(f(x))
Given: (i) f : R → R : f(x) = x2 + 2
f o g = f(g(x))
Ans) = 6
g o f = g(f(x))
⇒ g(x2+2)
Prove that the function f: R → R : f(x)= 2x is one-one and onto.
To prove: function is one-one and onto
Given: f: R → R : f(x)= 2x
We have,
f(x) = 2x
For, f(x1) = f(x2)
⇒ 2x1 = 2x2
⇒ x1 = x2
When, f(x1) = f(x2) then x1 = x2
∴ f(x) is one-one
f(x) = 2x
Let f(x) = y such that
⇒ y = 2x
Since ,
⇒ x will also be a real number, which means that every value of y is associated with some x
∴ f(x) is onto
Hence Proved
Prove that the function f: N → N : f (x)=3x is one-one and into.
To prove: function is one-one and into
Given: f: N → N : f(x)= 3x
We have,
f(x) = 3x
For, f(x1) = f(x2)
⇒ 3x1 = 3x2
⇒ x1 = x2
When, f(x1) = f(x2) then x1 = x2
∴ f(x) is one-one
f(x) = 3x
Let f(x) = y such that
⇒ y = 3x
If y = 1,
But as per question , hence x can not be
Hence f(x) is into
Hence Proved
Show that the function f : R → R : f (x) = x2 is neither one-one nor onto.
To prove: function is neither one-one nor onto
Given: f : R → R : f (x) = x2
Solution: We have,
f(x) = x2
For, f(x1) = f(x2)
⇒ x12 = x22
⇒ x1 = x2 or, x1 = -x2
Since x1 doesn’t has unique image
∴ f(x) is not one-one
f(x) = x2
Let f(x) = y such that
⇒ y = x2
If y = -1, as
Then x will be undefined as we cannot place the negative value under the square root
Hence f(x) is not onto
Hence Proved
Show that the function f : N → N : f (x) = x2 is one-one and into.
To prove: function is one-one and into
Given: f : N → N : f (x) = x2
Solution: We have,
f(x) = x2
For, f(x1) = f(x2)
⇒ x12 = x22
⇒ x1 = x2
Here we can’t consider x1 = -x2 as , we can’t have negative values
∴ f(x) is one-one
f(x) = x2
Let f(x) = y such that
⇒ y = x2
If y = 2, as
Then we will get the irrational value of x, but
Hence f(x) is not into
Hence Proved
Show that the function f : R → R : f (x) = x4 is neither one-one nor onto.
To prove: function is neither one-one nor onto
Given: f : R → R : f (x) = x4
We have,
f(x) = x4
For, f(x1) = f(x2)
⇒ x14 = x24
⇒ (x14 - x24) = 0
⇒(x12 - x22) (x12 + x22) = 0
⇒ (x1 - x2) (x1 + x2) (x12 + x22) = 0
⇒ x1 = x2 or, x1 = -x2 or, x12 = -x22
We are getting more than one value of x1 (no unique image)
∴ f(x) is not one-one
f(x) = x4
Let f(x) = y such that
⇒ y = x4
If y = -2, as
Then x will be undefined as we can’t place the negative value under the square root
Hence f(x) is not onto
Hence Proved
Show that the function f : Z → Z : f (x) = x3 is one-one and into.
To prove: function is one-one and into
Given: f : Z → Z : f (x) = x3
Solution: We have,
f(x) = x3
For, f(x1) = f(x2)
⇒ x13 = x23
⇒ x1 = x2
When, f(x1) = f(x2) then x1 = x2
∴ f(x) is one-one
f(x) = x3
Let f(x) = y such that
⇒ y = x3
If y = 2, as
Then we will get an irrational value of x, but
Hence f(x) is into
Hence Proved
Let R0 be the set of all nonzero real numbers. Then, show that the function is one-one and onto.
To prove: function is one-one and onto
We have,
For, f(x1) = f(x2)
⇒ x1 = x2
When, f(x1) = f(x2) then x1 = x2
∴ f(x) is one-one
Let f(x) = y such that
Since ,
⇒ x will also , which means that every value of y is associated with some x
∴ f(x) is onto
Hence Proved
Show that the function f : R → R : f(x) = 1 + x2 is many-one into.
To prove: function is many-one into
Given: f : R → R : f(x) = 1 + x2
We have,
f(x) = 1 + x2
For, f(x1) = f(x2)
⇒ 1 + x12 = 1 + x22
⇒ x12 = x22
⇒ x12 - x22 = 0
⇒ (x1 – x2) (x1 + x2) = 0
⇒ x1 = x2 or, x1 = –x2
Clearly x1 has more than one image
∴ f(x) is many-one
f(x) = 1 + x2
Let f(x) = y such that
⇒ y = 1 + x2
⇒ x2 = y – 1
If y = 3, as
Then x will be undefined as we can’t place the negative value under the square root
Hence f(x) is into
Hence Proved
Let be an invertible function. Find f-1.
To find: f-1
Given:
We have,
Let f(x) = y such that
⇒ 4y = 2x – 7
⇒ 4y + 7 = 2x
Let f : R → R : f(x) = 10x + 3. Find f-1.
To find: f-1
Given: f : R → R : f(x) = 10x + 3
We have,
f(x) = 10x + 3
Let f(x) = y such that
⇒ y = 10x + 3
⇒ y – 3 = 10x
Show that f is many-one and into.
To prove: function is many-one and into
We have,
f(x) = 1 when x is rational
It means that all rational numbers will have same image i.e. 1
⇒ f(2) = 1 = f (3) , As 2 and 3 are rational numbers
Therefore f(x) is many-one
The range of function is [{-1},{1}] but codomain is set of real numbers.
Therefore f(x) is into
Let f (x) = x + 7 and g(x) = x -7, x ∈ R. Find (f o g) (7).
To find: (f o g) (7)
Formula used: f o g = f(g(x))
Given: (i) f (x) = x + 7
(ii) g (x) = x – 7
We have,
f o g = f(g(x)) = f(x – 7) = [ (x – 7) + 7 ]
⇒ x
(f o g) (x) = x
(f o g) (7) = 7
Ans). (f o g) (7) = 7
Let f : R → R and g : R → R defined by f(x) = x2 and g(x) = (x + 1). Show that g o f ≠ f o g.
To prove: g o f ≠ f o g
Formula used: (i) f o g = f(g(x))
(ii) g o f = g(f(x))
Given: (i) f : R → R : f(x) = x2
(ii)
We have,
f o g = f(g(x)) = f(x + 7)
f o g = (x + 7)2 = x2 + 14x + 49
g o f = g(f(x)) = g(x2)
g o f = (x2 + 1) = x2 + 1
Clearly g o f ≠ f o g
Hence Proved
Let f : R → R : f(x) = (3 - x3)1/3. Find f o f.
To find: f o f
Formula used: (i) f o f = f(f(x))
Given: (i) f : R → R : f(x) = (3 - x3)1/3
We have,
f o f = f(f(x)) =
f o f =
=
=
=
= x
Ans) f o f (x) = x
Let f : R → R : f(x) = 3x + 2, find f{f(x)}.
To find: f{f(x)}
Formula used: (i) f o f = f(f(x))
Given: (i) f : R → R : f(x) = 3x + 2
We have,
f{f(x)} = f(f(x)) = f(3x + 2)
f o f =3(3x + 2) + 2
= 9x + 6 + 2
= 9x + 8
Ans) f{f(x)} = 9x + 8
Let f = {(1, 2), (3, 5), (4, 1)} and g = {(1, 3), (2, 3), (5, 1)). Write down g o f.
To find: g o f
Formula used: g o f = g(f(x))
Given: (i) f = {(1, 2), (3, 5), (4, 1)}
(ii) g = {(1, 3), (2, 3), (5, 1)}
We have,
gof(1) = g(f(1)) = g(2) = 3
gof(3) = g(f(3)) = g(5) = 1
gof(4) = g(f(4)) = g(1) = 3
Ans) g o f = {(1, 3), (3, 1), (4, 3)}
Let A = {1, 2, 3, 4} and f = {(1, 4), (2, 1) (3, 3), (4, 2)}. Write down (f o f).
To find: f o f
Formula used: f o f = f(f(x))
Given: (i) f = {(1, 4), (2, 1) (3, 3), (4, 2)}
We have,
fof(1) = f(f(1)) = f(4) = 2
fof(2) = f(f(2)) = f(1) = 4
fof(3) = f(f(3)) = f(3) = 3
fof(4) = f(f(4)) = f(2) = 1
Ans) f o f = {(1, 2), (2, 4), (3, 3), (4, 1)}
Let f(x) = 8x3 and g(x) = x1/3. Find g o f and f o g.
To find: g o f and f o g
Formula used: (i) f o g = f(g(x))
(ii) g o f = g(f(x))
Given: (i) f(x) = 8x3
(ii) g(x) = x1/3
We have,
g o f = g(f(x)) = g(8x3)
g o f = = 2x
f o g = f(g(x)) = f(x1/3)
f o g = = 8x
Ans) g o f = 2x and f o g = 8x
Let f : R → R : f(x) = 10x + 7. Find the function g : R → R : g o f = f o g = Ig.
To find: the function g : R → R : g o f = f o g = Ig
Formula used: (i) g o f = g(f(x))
(ii) f o g = f(g(x))
Given: f : R → R : f(x) = 10x + 7
We have,
f(x) = 10x + 7
Let f(x) = y
⇒ y = 10x + 7
⇒ y – 7 = 10x
Let where g: R → R
g o f = g(f(x)) = g(10x + 7)
= x
= Ig
f o g = f(g(x)) =
=
= x – 7 + 7
= x
Clearly g o f = f o g = Ig
Let A = {1, 2, 3), B = {4, 5, 6, 7) and let f = {(1, 4), (2,5), (3, 6)} be a function from A to B. State whether f is one-one.
To state: Whether f is one-one
Given: f = {(1, 4), (2,5), (3, 6)}
Here the function is defined from A → B
For a function to be one-one if the images of distinct elements of A under f are distinct
i.e. 1,2 and 3 must have a distinct image.
From f = {(1, 4), (2, 5), (3, 6)} we can see that 1, 2 and 3 have distinct image.
Therefore f is one-one
Ans) f is one-one
Let A = {2, 3, 4, 5} and B = {7, 9, 11, 13}, and
let f = {(2, 7), (3, 9), (4, 11), (5, 13)}.
Show that f is invertible and find f-1.
To Show: that f is invertible
To Find: Inverse of f
[NOTE: Any functions is invertible if and only if it is bijective functions (i.e. one-one and onto)]
one-one function: A function f : A B is said to be a one-one function or injective mapping if different elements of A have different images in B. Thus for xl, x2 A & f(x1), f(x2) B, f(x1) = f(x2) x1= x2 or x1 x2f(x1) f(x2)
onto function: If range = co-domain then f(x) is onto functions.
So, We need to prove that the given function is one-one and onto.
As we see that inthe above figure (2 is mapped with 7), (3 is mapped with 9), (4 is mapped with 11),
(5 is mapped with 13)
So it is one-one functions.
Now elements of B are known as co-domain. Also, a range of a function is also the elements of B(by definition)
So it is onto functions.
Hence Proved that f is invertible.
Now, We know that if f : A B then f-1 : B A (if it is invertible)
So,
So f-1 = {(7, 2), (9, 3), (11, 4), (13, 5)}
Show that the function f : R → R : f(x) = 2x + 3 is invertible and find f-1.
To Show: that f is invertible
To Find: Inverse of f
[NOTE: Any functions is invertible if and only if it is bijective functions (i.e. one-one and onto)]
one-one function: A function f : A B is said to be a one-one function or injective mapping if different elements of A have different images in B. Thus for x1, x2 A & f(x1), f(x2) B, f(x1) = f(x2) x1= x2 or x1 x2f(x1) f(x2)
onto function: If range = co-domain then f(x) is onto functions.
So, We need to prove that the given function is one-one and onto.
Let x1, x2 R and f(x) = 2x+3.So f(x1) = f(x2) 2x1+3 = 2x2+3 x1=x2
So f(x1) = f(x2) x1= x2, f(x) is one-one
Given co-domain of f(x) is R.
Let y = f(x) = 2x+3 , So x = [Range of f(x) = Domain of y]
So Domain of y is R(real no.) = Range of f(x)
Hence, Range of f(x) = co-domain of f(x) = R
So, f(x) is onto function
As it is bijective function. So it is invertible
Invers of f(x) is f-1(y) =
Let f : Q → Q : f(x) = 3x —4. Show that f is invertible and find f-1.
To Show: that f is invertible
To Find: Inverse of f
[NOTE: Any functions is invertible if and only if it is bijective functions (i.e. one-one and onto)]
one-one function: A function f : A B is said to be a one-one function or injective mapping if different elements of A have different images in B. Thus for x1, x2 A & f(x1), f(x2) B, f(x1) = f(x2) x1= x2 or x1 x2f(x1) f(x2)
onto function: If range = co-domain then f(x) is onto functions.
So, We need to prove that the given function is one-one and onto.
Let x1, x2 Q and f(x) = 3x-4.So f(x1) = f(x2) 3x1 - 4 = 3x2 - 4 x1=x2
So f(x1) = f(x2) x1= x2, f(x) is one-one
Given co-domain of f(x) is Q.
Let y = f(x) = 3x- 4 , So x = [Range of f(x) = Domain of y]
So Domain of y is Q = Range of f(x)
Hence, Range of f(x) = co-domain of f(x) = Q
So, f(x) is onto function
As it is bijective function. So it is invertible
Invers of f(x) is f-1(y) =
To Show: that f is invertible
To Find: Inverse of f
[NOTE: Any functions is invertible if and only if it is bijective functions (i.e. one-one and onto)]
one-one function: A function f : A B is said to be a one-one function or injective mapping if different elements of A have different images in B. Thus for x1, x2 A & f(x1), f(x2) B, f(x1) = f(x2) x1= x2 or x1 x2f(x1) f(x2)
onto function: If range = co-domain then f(x) is onto functions.
So, We need to prove that the given function is one-one and onto.
Let x1, x2 Q and f(x) = .So f(x1) = f(x2) = x1=x2
So f(x1) = f(x2) x1= x2, f(x) is one-one
Given co-domain of f(x) is R.
Let y = f(x) =, So x = [Range of f(x) = Domain of y]
So Domain of y is R = Range of f(x)
Hence, Range of f(x) = co-domain of f(x) = R
So, f(x) is onto function
As it is bijective function. So it is invertible
Invers of f(x) is f-1(y) =
If show that (f o f) (x) = x for all
Hence, find f-1.
To Show: that f o f (x) = x
Finding (f o f) (x) == ==.
Show that the function f on defined as is one-one and onto. Hence, find f-1.
To Show: that f is one-one and onto
To Find: Inverse of f
[NOTE: Any functions is invertible if and only if it is bijective functions (i.e. one-one and onto)]
one-one function: A function f : A B is said to be a one-one function or injective mapping if different elements of A have different images in B. Thus for x1, x2 A & f(x1), f(x2) B, f(x1) = f(x2) x1= x2 or x1 x2f(x1) f(x2)
onto function: If range = co-domain then f(x) is onto functions.
So, We need to prove that the given function is one-one and onto.
Let x1, x2 Q and f(x) = .So f(x1) = f(x2) = on solving we get x1=x2
So f(x1) = f(x2) x1= x2, f(x) is one-one
Given co-domain of f(x) is R except 3x-2=0.
Let y = f(x) = So x = [Range of f(x) = Domain of y]
So Domain of y is R (except 3x-2=0) = Range of f(x)
Hence, Range of f(x) = co-domain of f(x) = R except 3x-2=0
So, f(x) is onto function
As it is bijective function. So it is invertible
Invers of f(x) is f-1(y) = .
Show that the function f on into itself, defined by is one-one and onto. Hence, find f-1.
To Show: that f is one-one and onto
To Find: Inverse of f
[NOTE: Any functions is invertible if and only if it is bijective functions (i.e. one-one and onto)]
one-one function: A function f : A B is said to be a one-one function or injective mapping if different elements of A have different images in B. Thus for x1, x2 A & f(x1), f(x2) B, f(x1) = f(x2) x1= x2 or x1 x2f(x1) f(x2)
onto function: If range = co-domain then f(x) is onto functions.
So, We need to prove that the given function is one-one and onto.
Let x1, x2 Q and f(x) = .So f(x1) = f(x2) = on solving we get x1=x2
So f(x1) = f(x2) x1= x2, f(x) is one-one
Given co-domain of f(x) is R except 3x+4=0.
Let y = f(x) = So x = [Range of f(x) = Domain of y]
So Domain of y is R = Range of f(x)
Hence, Range of f(x) = co-domain of f(x) = R except 3x+4=0
So, f(x) is onto function
As it is bijective function. So it is invertible
Invers of f(x) is f-1(y) =
Let R+ be the set of all positive real numbers. show that the function f : R+→ [-5, ∞]: f(x) = (9x2 + 6x – 5) is invertible. Find f-1.
To Show: that f is invertible
To Find: Inverse of f
[NOTE: Any functions is invertible if and only if it is bijective functions (i.e. one-one and onto)]
one-one function: A function f : A B is said to be a one-one function or injective mapping if different elements of A have different images in B. Thus for x1, x2 A & f(x1), f(x2) B, f(x1) = f(x2) x1= x2 or x1 x2f(x1) f(x2)
onto function: If range = co-domain then f(x) is onto functions.
So, We need to prove that the given function is one-one and onto.
Let x1, x2 R and f(x) = (9x2 + 6x – 5).So f(x1) = f(x2) (92 + 6 – 5) = (92 + 6 – 5) on solving we get x1=x2
So f(x1) = f(x2) x1= x2, f(x) is one-one
Given co-domain of f(x) is [-5, ∞]
Let y = f(x) = (9x2 + 6x – 5), So x = [Range of f(x) = Domain of y]
So Domain of y = Range of f(x) = [-5, ∞]
Hence, Range of f(x) = co-domain of f(x) =[-5, ∞]
So, f(x) is onto function
As it is bijective function. So it is invertible
Invers of f(x) is f-1(y) =.
Let f : N → R : f(x) = 4x2 + 12x + 15. Show that f: N → range (f) is invertible. Find f-1.
To Show: that f is invertible
To Find: Inverse of f
[NOTE: Any functions is invertible if and only if it is bijective functions (i.e. one-one and onto)]
one-one function: A function f : A B is said to be a one-one function or injective mapping if different elements of A have different images in B. Thus for x1, x2 A & f(x1), f(x2) B, f(x1) = f(x2) x1= x2 or x1 x2f(x1) f(x2)
onto function: If range = co-domain then f(x) is onto functions.
So, We need to prove that the given function is one-one and onto.
Let x1, x2 R and f(x) = 4x2 + 12x + 15 So f(x1) = f(x2) (42 + 12 +1 5) = (42 + 12 +1 5), on solving we get x1=x2
So f(x1) = f(x2) x1= x2, f(x) is one-one
Given co-domain of f(x) is Range(f).
Let y = f(x) = 4x2 + 12x + 15, So x = [Range of f(x) = Domain of y]
So Domain of y = Range of f(x) = [6, ∞]
Hence, Range of f(x) = co-domain of f(x) = [6, ∞]
So, f(x) is onto function
As it is bijective function. So it is invertible
Invers of f(x) is f-1(y) =.
Let A = R – {2} and B = R – {1}. If show that f is one-one and onto. Hence, find f-1.
To Show: that f is one-one and onto
To Find: Inverse of f
[NOTE: Any functions is invertible if and only if it is bijective functions (i.e. one-one and onto)]
one-one function: A function f : A B is said to be a one-one function or injective mapping if different elements of A have different images in B. Thus for x1, x2 A & f(x1), f(x2) B, f(x1) = f(x2) x1= x2 or x1 x2f(x1) f(x2)
onto function: If range = co-domain then f(x) is onto functions.
So, We need to prove that the given function is one-one and onto.
Let x1, x2 Q and f(x) = .So f(x1) = f(x2) = , on solving we get x1=x2
So f(x1) = f(x2) x1= x2, f(x) is one-one
Given co-domain of f(x) is R – {1}
Let y = f(x) =, So x = [Range of f(x) = Domain of y]
So Domain of y = Range of f(x) = R – {1}
Hence, Range of f(x) = co-domain of f(x) = R – {1}.
So, f(x) is onto function
As it is a bijective function. So it is invertible
Invers of f(x) is f-1(y) =
Let f and g be two functions from R into R, defined by f(x) = |x| + x and g(x) = |x| - x for all x ∈ R. Find f o g and g o f.
To Find: Inverse of f o g and g o f.
Given: f(x) = |x| + x and g(x) = |x| - x for all x ∈ R
f o g (x) = f(g(x)) = |g(x)| + g(x) = ||x| - x | + |x| - x
Case 1) when x0
f(g(x)) = 0 (i.e. |x| - x)
Case 2) when x 0
f(g(x)) = -4x
g o f (x) = g(f(x)) = |f(x)| - f(x) = ||x| + x | - |x| - x
Case 1) when x0
g(f(x)) = 0 (i.e. |x| - x)
Case 2) when x 0
g(f(x)) = 0
Mark (√) against the correct answer in the following:
f : N → N : f(x) = 2x is
A. one - one and onto
B. one - one and into
C. many - one and onto
D. many - one and into
f(x) = 2x
For One - One
f(x1) = 2x1
f(x2) = 2x2
put f(x1) = f(x2) we get
2x1 = 2x2
Hence, if f(x1) = f(x2), x1 = x2
Function f is one - one
For Onto
f(x) = 2x
let f(x) = y, such that y∈N
2x = y
⇒
If y = 1
x =
which is not possible as x∈N
Hence, f is not onto., f is into
Hence, option b is correct
Mark (√) against the correct answer in the following:
f : N → N : f(x) = x2 + x + 1 is
A. one - one and onto
B. one - one and into
C. many - one and onto
D. many - one and into
In the given range of N f(x) is monotonically increasing.
∴f(x) = x2 + x + 1 is one one.
But Range of f(n) = [0.75,∞)≠N(codomain)
Hence, f(x) is not onto.
Hence, the function f : N → N : f(x) = (x2 + x + 1) is one - one but not onto. i.e. into
Mark (√) against the correct answer in the following:
f : R → R : f(x) = x2 is
A. one - one and onto
B. one - one and into
C. many - one and onto
D. many - one and into
f(x) = x2
⇒y = x2
in this range the lines cut the curve in 2 equal valued points of y, therefore, the function f(x) = x2 is many - one .
Range of f(x) = (0,∞)≠R(codomain)
∴f(x) is into
∴ f : R → R: f(x) = x2 is many - one into
Mark (√) against the correct answer in the following:
f : R → R : f(x) = x3 is
A. one - one and onto
B. one - one and into
C. many - one and onto
D. many - one and into
f(x) = x3
Since the function f(x) is monotonically increasing from the domain R → R
∴f(x) is one –one
Range of f(x) = ( - ∞,∞)≠R(codomain)
∴f(x) is into
∴ f : R → R: f(x) = x3 is one - one into.
Mark (√) against the correct answer in the following:
f : R + → R + : f(x) = ex is
A. many - one and into
B. many - one and onto
C. one - one and into
D. one - one and onto
f(x) = ex
Since the function f(x) is monotonically increasing from the domain R + → R +
∴f(x) is one –one
Range of f(x) = (1,∞) = R + (codomain)
∴f(x) is onto
∴ f : R + → R + : f(x) = ex is one - one onto.
Mark (√) against the correct answer in the following:
is
A. one - one and into
B. one - one and onto
C. many - one and into
D. many - one and onto
Here in this range, the function is NOT repeating its value,
Therefore it is one - one.
Range = Codomain
∴Function is onto
Hence, option B is the correct choice.
Mark (√) against the correct answer in the following:
f : R → R : f(x) = cos x is
A. one - one and into
B. one - one and onto
C. many - one and into
D. many - one and onto
f(x) = cosx
y = cosx
Here in this range the lines cut the curve in many equal valued points of y therefore the function f(x) = cosx is not one - one.
⇒f(x) = many one
Range of f(x) = [ - 1,1]≠R(codomain)
∴f(x) is not onto.
⇒f(x) = into
Hence,f(x) = cosx is many one and into
Ans: (c) many - one and into
Mark (√) against the correct answer in the following:
f : C → R : f(z) = |z| is
A. one - one and into
B. one - one and onto
C. many - one and into
D. many - one and onto
Here in this range the lines cut the curve in 2 equal valued points of y therefore the function f(z) = |z| is not one - one
⇒f(z) = many one.
Range of f(z) = [0,∞)≠R(codomain)
∴f(z) is not onto.
⇒f(z) = into
Hence, f(z) = |z| is many one and into
Mark (√) against the correct answer in the following:
Let A = R – {3} and B = R – {1}. Then is
A. one - one and into
B. one - one and onto
C. many - one and into
D. many - one and onto
In this function
x = 3 and y = 1 are the asymptotes of this curve and these are not included in the functions of the domain and range respectively therefore the function f(x) is one one sice there are no different values of x which has same value of y .
and the function has no value at y = 1 here range = codomain
∴f(x) is onto
Mark (√) against the correct answer in the following:
Let A and B be two non - empty sets and let
f : (A × B) → (B × A) : f(a, b) = (b, a). Then, f is
A. one - one and into
B. one - one and onto
C. many - one and into
D. many - one and onto
SINCE, f(a, b) = (b, a).There is no same value of y at different values of x ∴function is one one
∴Range(A×B)≠Codomain(B × A)
⇒function is into
Mark (√) against the correct answer in the following:
Let f : Q → Q : f(x) = (2x + 3). Then, f - 1(y) = ?
A. (2y - 3)
B.
C.
D. none of these
f(x) = 2x + 3
⇒y = 2x + 3
x⟺y
⇒x = 2y + 3
⇒x - 3 = 2y
⇒
x⟺y
⇒
Mark (√) against the correct answer in the following:
Let Then f - 1(y) = ?
A.
B.
C.
D. None of these
f(x) =
⇒y =
x⟺y
⇒x =
⇒3yx + 4x = 4y
⇒y(3x - 4) = - 4x
⇒y =
x⟺y
⇒x =
Mark (√) against the correct answer in the following:
If then (f o f) (x) = ?
A. x
B. (2x - 3)
C.
D. None of these
Mark (√) against the correct answer in the following:
If f(x) = (x2 – 1) and g(x) = (2x + 3) then (g o f) (x) = ?
A. (2x2 + 3)
B. (3x2 + 2)
C. (2x2 + 1)
D. None of these
f(x) = (x2 – 1)
g(x) = (2x + 3)
∴(g o f) (x) = g(f(x))
Mark (√) against the correct answer in the following:
If then f(x) = ?
A. x2
B. (x2 – 1)
C. (x2 – 2)
D. None of these
Mark (√) against the correct answer in the following:
If then (f o f o f) (x) = ?
A.
B.
C. x
D. None of these
Mark (√) against the correct answer in the following:
If then (f o f) (x) = ?
A.
B. x
C.
D. None of these
Mark (√) against the correct answer in the following:
If f(x) = x2 – 3x + 2 then (f o f) (x) = ?
A. x4
B. x4 – 6x3
C. x4 – 6x3 + 10x2
D. None of these
f(x) = x2 – 3x + 2
⇒f(x) = x2 - 2x - x + 2 = x(x - 2) - 1(x - 2)
⇒f(x) = (x - 2)(x - 1)
⇒f(x) = (x - 2)(x - 1)
⇒f(f(x)) = ( f(x) - 2)( f(x) - 1)
⇒f(f(x)) = ((x - 2)(x - 1) - 2) ((x - 2)(x - 1) - 1)
⇒f(f(x)) = (x2 – 3x + 2 - 2) (x2 – 3x + 2 - 1)
⇒f(f(x)) = (x2 – 3x) (x2 – 3x + 1)
⇒f(f(x)) = x4 - 3x3 + x2 - 3x3 + 9x2 - 3x
⇒f(f(x)) = x4 - 6x3 + 10x2 - 3x
Mark (√) against the correct answer in the following:
If f(x) = 8x3 and g(x) = x1/3 then (g o f) (x) = ?
A. x
B. 2x
C.
D. 3x2
f(x) = 8x3
g(x) = x1/3
Mark (√) against the correct answer in the following:
If f(x) = x2, g(x) = tan x and h(x) = log x then
A. 0
B. 1
C.
D.
f(x) = x2, g(x) = tan x and h(x) = log x
Mark (√) against the correct answer in the following:
If f = {(1, 2), (3, 5), (4, 1)} and g = {(2, 3), (5, 1), (1, 3)} then (g o f) = ?
A. {(3, 1), (1, 3), (3, 4)}
B. {(1, 3), (3, 1), (4, 3)}
C. {(3, 4), (4, 3), (1, 3)}
D. {(2, 5), (5, 2), (1, 5)}
g = {(2, 3), (5, 1), (1, 3)}
(g o f) = {(dom(f), 3), (dom(f), 1), (dom(f), 3)}
⇒(g o f) = {(1, 3), (3, 1), (4, 3)}
Mark (√) against the correct answer in the following:
Let Then, dom (f) = ?
A. [ - 3, 3]
B. [ - ∞, - 3]
C. [3, ∞)
D. ( - ∞, - 3] ∪ (4, ∞)
F(x) =
∴dom(f) = [ - 3, 3]
Mark (√) against the correct answer in the following:
Let Then, dom (f) - ?
A. [1, 4)
B. [1, 4]
C. ( - ∞, 4]
D. ( - ∞, 1] ∪ (4, ∞)
And x≠4
Mark (√) against the correct answer in the following:
Let Then, dom (f) = ?
A. ( - ∞, 1]
B. [ - 1, ∞)
C. (1, ∞)
D. ( - ∞, - 1] ∪ (1, ∞)
And
Taking the intersection we get
Dom(f) = (1, ∞)
Mark (√) against the correct answer in the following:
Let Then, dom (f) = ?
A. R
B. R – {1}
C. R – { - 1}
D. R – { - 1, 1}
X2 - 1≠0
x≠(1, - 1)
∴ Dom(f) = R - { - 1,1}
Mark (√) against the correct answer in the following:
Let . Then, dom (f) = ?
A. (-1, 1)
B. [-1, 1]
C. [-1, 1] – {0}
D. none of these
Given:
From f(x), x ≠ 0
Now, domain of sin-1x is [-1, 1] as the values of sin-1x lies between -1 and 1.
We can see that from this graph:
Domain of f(x) = [-1, 1] – 0
Hence, B is the correct answer.
Mark (√) against the correct answer in the following:
Let f(x) = cos - 1 2x. Then, dom (f) = ?
A. [ - 1, 1]
B.
C.
D.
f(x) = cos - 1 2x.
domain of cos - 1x = [ - 1,1]
on multiplying by an integer the domain decreases by same number
domain of cos - 12x = [ - 1/2,1/2]
Mark (√) against the correct answer in the following:
Let f(x) = cos - 1(3x – 1). Then, dom (f) = ?
A.
B.
C.
D. None of these
f(x) = cos - 1 (3x - 1).
domain of cos - 1x = [ - 1,1]
on multiplying by an integer the domain decreases by same number
domain of cos - 13x = [ - 1/3,1/3]
domain of cos - 1 (3x - 1) = [1/3 - 1/3,1/3 + 1/3] = [0,2/3]
Mark (√) against the correct answer in the following:
Let f(x) = √cos x. Then, dom (f) = ?
A.
B.
C.
D. none of these
As per the diagram
We can imply that domain of √cosx
is
Mark (√) against the correct answer in the following:
Let f(x) = √log (2x – x2). Then, dom (f) = ?
A. (0, 2)
B. [1, 2]
C. ( - ∞, 1]
D. None of these
f(x) = √log (2x – x2).
Dom(f) = ( - ∞, 1)
Mark (√) against the correct answer in the following:
Let f(x) = x2. Then, dom (f) and range (f) are respectively.
A. R and R
B. R + and R +
C. R and R +
D. R and R – {0}
According to sketched graph of x2
Domain of f(x) = R
And Range of f(x) = R +
Mark (√) against the correct answer in the following:
Let f(x) = x3. Then, dom (f) and range (f) are respectively
A. R and R
B. R + and R +
C. R and R +
D. R + and R
According to sketched graph of x3
Domain of f(x) = R
And Range of f(x) = R
Since x3 is a, monotonically increasing function
Mark (√) against the correct answer in the following:
Let f(x) = log (1 – x) + √x2 – 1. Then, dom (f) = ?
A. (1, ∞)
B. ( - ∞, - 1]
C. [ - 1, 1)
D. (0, 1)
log (1 – x) + √(x2 – 1)
1 - x>0
X2 - 1≥0
X21
Taking intersection of the ranges we get
Dom (f) = (b) ( - ∞, - 1]
Mark (√) against the correct answer in the following:
Let Then, range (f) = ?
A. ( - ∞, 1]
B. [1, ∞)
C. [ - 1, 1]
D. none of these
∴ range (f) = [1, ∞)
Mark (√) against the correct answer in the following:
Let Then, range (f) = ?
A. [1, ∞)
B. [0, 1)
C. [ - 1, 1]
D. (0, 1]
⇒y≥0
And
1 - y>0
⇒y<1
Taking intersection we get
range (f) = [0, 1)
Mark (√) against the correct answer in the following:
The range of is
A. [ - 2, 2]
B. [2, ∞)
C. ( - ∞, - 2]
D. none of these
For this type
Range is
Mark (√) against the correct answer in the following:
The range of f(x) = ax, where a > 0 is
A. [ - ∞, 0]
B. [ - ∞, 0)
C. [0, ∞)
D. (0, ∞)
f(x) = ax
when x<0
0<ax<1
When x≥0
ax>0
Therefore range of f(x) = ax = (0, ∞)
Mark (√) against the correct answer in the following:
Let
Then, f is
A. one - one and into
B. one - one and onto
C. many - one and into
D. many - one and onto
f(1) = 1
f(2) = 1
f(3) = 2
f(4) = 2
f(5) = 3
f(6) = 3
Since at different values of x we get same value of y ∴f(n) is many –one
And range of f(n) = N = N(codomain)
∴ the function f: N → Z, defined by
is both many - one and onto.
Mark (√) against the correct answer in the following:
Let f : N → X : f(x) = 4x2 + 12x + 15. Then, f - 1(y) = ?
A.
B.
C.
D. None of these
f(x) = 4x2 + 12x + 15
⇒y = 4x2 + 12x + 15
⇒y = (2x + 3)2 + 6
⇒√(y - 6) = 2x + 3
⇒
f - 1(y) =